Parathyroid cyst eclipsed by parathyroid adenoma: Value of adjunct imaging - Bhatia, Khyati; Sarin, Deepak; Singh, Gopal Kumar; Singhal, Alka Ashmita (Indian Journal of Radiology and Imaging, 2020)
Parathyroid cyst is a rare clinical entity and often presents as a diagnostic challenge, especially when presents in conjunction with a coexistent parathyroid adenoma. Patient with primary hyperparathyroidism had presented with a localised left inferior parathyroid adenoma with a coexistent right inferior parathyroid cyst which was initially missed on routine ultrasound and sestamibi scan. Suspicion of right inferior thyroid cyst was raised on ultrasound done by a dedicated parathyroid ultrasonologist. Right inferior thyroid cyst was confirmed to be parathyroid cyst on histopathological examination. Parathyroid cysts are seldom picked on sestamibi due to compressed parathyroid tissue present only at the periphery of the cyst. Hence, use of adjunct anatomical imaging like ultrasound, CT scan or MRI is worthwhile to reduce chances of missing hyperfunctional parathyroid tissue, which can eventually lead to revision surgery for persistent primary hyperparathyroidism.
Keywords: Parathyroid adenoma; parathyroid cyst; sestamibi; ultrasound